An aqueous manganese–lead battery for large-scale energy storage. Issue 12 (10th March 2020) - Huang, Jianhang; Yan, Lei; Bin, Duan; Dong, Xiaoli; Wang, Yonggang; Xia, Yongyao
Abstract : A manganese–lead battery based on MnO2 /Mn 2+ cathodic reaction and PbSO4 /Pb anodic reaction was demonstrated. With an optimized deposition behavior and high solubility of MnO2, high areal capacity (50 mA h cm −2 ) and energy density (187 W h L −1 ) can be obtained. Abstract : With the increase in interest in energy storage for grid applications, a rechargeable battery, as an efficient energy storage/conversion system, has been receiving great attention. However, its development has largely been stalled by the issues of high cost, safety and energy density. Here, we report an aqueous manganese–lead battery for large-scale energy storage, which involves the MnO2 /Mn 2+ redox as the cathode reaction and PbSO4 /Pb redox as the anode reaction. The redox mechanism of MnO2 /Mn 2+ was investigated to improve reversibility. All materials are inexpensive and the assembled battery can work well during the penetration test. The battery shows a discharge voltage of around 1.55 V, high rate capability, and no obvious capacity decay over 10 000 cycles. Furthermore, a high volumetric low energy density of 187 W h L −1 was obtained for a pouch battery using a high-concentration electrolyte comprising 3 M MnSO4 . Meanwhile, the low freezing point of the high-concentration electrolyte endowed the battery with capability to work at a low temperature of −40 °C. Owing to the low cost and high electrochemical performance, the Mn–Pb battery has great potential for grid energy storage.